DESPOTISM VS. DEMOCRACY IN THE MENA REGION - Kayrouz, Akl; Atala, Issam (European Scientific Journal, ESJ, 2015)
Since its birth on the planet Earth, man has incessantly embarked on a long journey in search of its â€œbeingâ€. He formed tribal clans, fought endless series of wars in search of wealth and power. He attempted to discover, understand and subdue the universe to its limited mind. His imagination created then herds of good and bad gods to hide his weaknesses, fears and limitations. Often, he proclaimed himself divine and godly, when, in reality he lives in fear and anxiety facing death and threats by unseen killer bacteria or natural elements that impacted and reduced his pride, arrogance, and self-worship to ultimate death. Glory, wealth, power, and physical well being soon evaporated into some dark and narrow dungeon. This self-proclaimed superman-woman, who defies all laws and rules, keep dreaming about being eternal, while reality transforms them sometimes into weak, empty and helpless vegetables. Their worlds of violence, threats and greed continually collapsed for no return. This research focuses upon this self-proclaimed â€œsuperhumanâ€ of the Middle East, who lives and dies in a state of slavery not imposed upon him by force, rather a result of personal consent. The authors aim to clarify the paradigm of relationship between despotism and consent.